(untitled) (INTERNATIONAL CONFERENCE ON MEDICINE, SCIENCE, AND EDUCATION, 2025)
According to literature data, trophoblastic disease is characteristic only of pregnant women of reproductive age and occurs in 0.1-0.25% of all pregnancies. Cystic fibrosis is most often diagnosed among this pathology.